2015
DOI: 10.1177/0148607115606116
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia During Home Parenteral Nutrition Administration in Patients Without Diabetes

Abstract: Hyperglycemia is a common finding with the use of PN in both the hospital and ambulatory setting in patients without a previous diagnosis of DM2. Age was the most significant predictor of the requirement of insulin in the present study. When hyperglycemia is managed appropriately with insulin therapy, the long-term complications can be minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Hyperglycemia is the most common complication of PN, especially at the beginning of therapy when patients are often acutely ill and malnournished 41 , 42 . The production of cytokines and counterregulatory hormones (eg, cortisol, epinephrine, glucagon, growth hormone) is upregulated during periods of stress or inflammation.…”
Section: Short‐term Metabolic Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hyperglycemia is the most common complication of PN, especially at the beginning of therapy when patients are often acutely ill and malnournished 41 , 42 . The production of cytokines and counterregulatory hormones (eg, cortisol, epinephrine, glucagon, growth hormone) is upregulated during periods of stress or inflammation.…”
Section: Short‐term Metabolic Complicationsmentioning
confidence: 99%
“…Although hyperglycemia is commonly seen in patients receiving HPN, it does not appear to increase the risk of developing diabetes, and the impact on long‐term outcomes is unknown. Edakkanambeth Varayil et al 41 found that nearly 42% of their HPN patients developed hyperglycemia that required insulin. Incidence of hyperglycemia did not affect long‐term outcomes 41 .…”
Section: Short‐term Metabolic Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…While lifesaving for many, HPEN does have risk of life‐threatening complications 7 , 8 , 52 59 . Advances in nutrition care options have helped decrease risk of bloodstream infection, but patients can still experience bloodstream or skin and soft tissue infection with either enteral or parenteral access 53 , 56 , 60 .…”
Section: Benefits Of the Guidelinesmentioning
confidence: 99%